Effect of Fermentation Time on Nutritional, Microbiological, and Sensorial Properties of Roselle Kefir Popsicle - Mohd Rozali, Nur Anisya Faten; Windayani, Neneng; Sunarharum, Wenny Bekti; Romli, Siti Rashima; MD Sikin, Adi; Wan Kamarudin, Wan Saidatul Syida (Jurnal Pangan dan Agroindustri, 2025)
The fermentation time plays a crucial role in the development of functional properties in fermented products, including kefir. This study investigates the effect of fermentation time on the nutritional, microbiological, and sensory properties of Roselle-based kefir popsicles. Fermentation times of 0, 18, 24, and 30 hours were analyzed for changes in acidity, viscosity, turbidity, fat content, ash content, Total Phenolic Content (TPC), Total Flavonoid Content (TFC), anthocyanins, antioxidant activity, calcium concentration, and Lactobacillus spp. population. Sensory evaluation assesses consumer preferences based on appearance, mouthfeel, flavor, aroma, color, and overall acceptance. The results showed that longer fermentation times, especially 30 hours, increased acidity, viscosity, and other nutritional parameters. However, popsicles fermented for 18 hours were most preferred by consumers due to their balanced sensory attributes. This study highlights the role of fermentation time in enhancing both the nutritional value and sensory appeal of Kefir Roselle-based popsicles, suggesting their potential as functional foods.